Safe Generation and Direct Use of Diazoesters in Flow Chemistry - Müller, Simon T. R.; Smith, Daniel; Hellier, Paul; Wirth, Thomas (Synlett, 2014)
A safe and fast method for the production of β-hydroxy-α-diazoesters in continuous flow technology is described. The synthesis involves the formation of ethyl diazoacetate in situ and the addition to several aldehydes in a two-step continuous flow microreactor setup. Rhodium acetate catalyzes a subsequent 1,2-hydride shift to give access to β-keto esters in a three-step sequence.
Keywords: addition; aldehydes; diazo compounds; flow chemistry; rhodium